Software Engineering Research, Management and Applications - Lee, Roger; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book gathers 12 of the most promising papers presented at the 15th International Conference on Software Engineering, Artificial Intelligence Research, Management and Applications (SERA 2017) held on June 7-9, 2017 at the University of Greenwich, London, UK. The aim of this conference was to bring together researchers and scientists, businessmen and entrepreneurs, teachers, engineers, computer users, and students to discuss the numerous fields of computer science, to share their experiences and to exchange new ideas and information in a meaningful way. The book also presents research findings regarding all aspects (theory, applications and tools) of computer and information science, and discusses the practical challenges encountered along the way and the solutions adopted to solve them.
Agile Web Development Methodologies: A Survey and Evaluation -- Load Experiment of the vDACS Scheme in case of Increasing the simultaneous connection for the DACS SV -- Blind Channel Estimation Using Novel Independent Component Analysis with Pulse Shaping for Interference Cancellation -- Anticipated Test Design and its Application to Evaluate and Select Embedded Libraries -- Improving Web Application Reliablilty and Testing Using Accurate Usage Models -- C-PLAD-SM: Extending Component Requirements with Use Cases and State Machines -- A Structural Rule-Based Approach for Design Patterns Recovery -- DRSS: Distributed RDF SPARQL Streaming -- An Efficient Approach for Real-Time Processing of RDSZ-Based Compressed RDF Streams -- Energy Efficiency Cluster Head Election Using Fuzzy Logic Method for Wireless Sensor Networks -- Enabling GSD Task Allocation via Cloud-based Software Processes -- Composite Event Handling over a Distributed Event-Based System.
Keywords: Computational intelligence; Software engineering; Artificial intelligence; Computational Intelligence; Software Engineering; Artificial Intelligence